MOTIVASI BELAJAR SISWA PADA MASA PANDEMI COVID 19 DI SDN BAJANG 01 KABUPATEN BLITAR - Ria Fajrin Rizqy Ana (Universitas PGRI Adi Buana Surabaya, 2022)
Learning motivation is the overall driving force in students that causes learning activities. The problem that occurs is that students experience a lack of motivation to learn due to parental attention, inefficient learning media, and supporting facilities in the learning process during the Covid 19 pandemic. The purpose of this study was to analyze students' learning motivation during the pandemic. The type of research used is qualitative. The subjects used were teachers and fourth grade students at SDN Bajang 01. The instruments included questionnaires, interviews and documentation. Data analysis techniques are data reduction, data presentation, verification. Based on the results of research and discussion of student learning motivation during the Covid 19 pandemic at SDN Bajang 01, it was included in the very high category with reference to 6 indicators, namely the desire and desire to succeed, the second indicator was encouragement and need for learning, the third indicator was hopes and dreams. future aspirations, the fourth indicator is appreciation in learning, the fifth indicator is interesting activities in learning, the sixth indicator is a conducive learning environment. The results of this study can be used as a consideration, especially for teachers who are able to increase student motivation, especially during the Covid 19 pandemic.